FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MIGRAN MELAKUKAN MOBILITAS NON PERMANEN KE KOTA DENPASAR - Rustariyuni, Surya Dewi (PIRAMIDA; Vol 9, No. 2 Desember 2013, 2013)
Many people come to do migration to Denpasar city because of Regional Wage of Minimum (UMR) in Denpasar city every years always higher than another region in Bali. The migrant because of economy motive move on Denpasar city and because many facilitation there are many kind of job, health fasility, education fasility, fasility of transportation, fasility of entertainer for adult and children also another fasility in which there are be the most pull factor for another region. This research aims to know impact the wage, time to do mobility, age and education for parsial and simultan to migration sircular in Denpasar city. To know which one the variable dominant to migrant sircular in Denpasar. This research method use primary data with binary logistic analysis because the variable is dichotomy, use dummy variable, the dependent variable is combination between matrix and nominal (non matrix). Probability method sampling used in this research is proportional stratified randome sampling. From the solvin calculate, the result for sampling 82,17 be 82 people but this research use 90 people. The location of research in Denpasar city because of many worker (migrant) do mobility. The population is they are come from another city of Denpasar, isn’t live in Denpasar, the meaning is they are have identity card not in Denpasar but work in Denpasar city. The result is age, education, time to mobility and wage variable simultanity and parsial, significance to habit migration to Denpasar. Education and wage variable have positif sign to habit migration to Denpasar. Government do the good development in all region until have minus migration in Denpasar. The people given knowledge for workshop, training, for increase the power of entrepreneur and government give lender for the first enterpreneur, policy of second father, and the simplicity for get lending.
Keywords: circular mobility; education; age; equitable of development